Language Games in ask.fm Conversations - Tania Alifianita; Triyono Lukmantoro, S.Sos, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The social media becomes a whole new way of communication which is very popular in any level of individuals. It is because, through social media, we can share not only information, but also values, dan actions which are transmitted rapidly across social and cultural limitations. One of the most popular social media among youth in Indonesia is ask.fm, which has question-answer type of interaction. If we look at ask.fm conversation in a glance, there is a harmonic involvement between personal, social, and cultural element in message interpreting. In Indonesia, conversation about SARA and gender through social media should be held in careful way, but otherwise it is been discussed in casual way by using language games. Ethnicity, Religion, Race, Inter-group relation (termed SARA) and gender issues are under the spotlight in this research, because these kind of issues can be discussed in very casual situation eventhough they are considered as sensitive issues and potentially building conflicts. The objectives of the research are describing and understanding language games in conversation of ask.fm, especially the SelebAsk’s profiles. This research uses qualitative method as well as conversation analysis, and using Language Games Theory as a main theory supported by New Media Theory, Computer Mediated Communication Theory, and Symbolic Interactionism Theory. This research showed us that humourous kind of language games are commonly used by SelebAsk while discussing about SARA and gender issues. Because humour basically has the stress relieving function which is very effective dan could be transmitted spontaneously. Incompatibility or incongruity between reader’s expectation and SelebAsk’s utterances is the key to humorous conversation. There is superiority meaning within humorous language games which leads to human’s natural characteristic as competitive and gluttonous for power. However in conversation of ask.fm, SelebAsk commonly use language games genuinely just for fun, achieving amusements without any intentions of hurting other groups.Aside from humour, sarcasm language game is also used as a form of superiority or vanity of particular culture or individual’s personality, and as a verbal aggression towards other groups.